Creative resource utilization in rural settings: The urinary catheter as a cholecystostomy tube - Taha Mollah; Shanthapriya Tellambura (Journal of Surgical Specialties and Rural Practice, 2022)
Cholecystostomy tubes are an established treatment option for patients with acute cholecystitis who are considered high risk for cholecystectomy. This is typically done as an interventional radiology procedure through a pigtail catheter inserted percutaneously. A 63-year-old diabetic male presented to our remote Emergency Department in rural North-Western Victoria (Modified Monash Model 4), with severe, stabbing epigastric pain. Despite normal bloods and imaging, the patient became progressively unwell necessitating a diagnostic laparoscopy and open conversion, which revealed acute acalculous gangrenous cholecystitis. A cholecystectomy was attempted and subsequently abandoned as safe dissection within Calot's triangle, without damaging biliary structures, was not possible. Based on the limited available resources at our rural center, a urinary (Foley) catheter was placed in the gallbladder and Hartmann's pouch sutured around it to act as a temporizng cholecystostomy tube while awaiting transfer to a tertiary center. The Foley catheter was removed after 6 weeks with no further intervention required with the patient making a full recovery. Compared to patients in urban areas, rural residents are more likely to experience health-care disadvantages, including increased likelihood to undergo procedures by specialists operating outside of their scope of practice and higher rates of emergency-related intensive care unit admissions. Despite this, and regardless of acuity, specialist availability, or resource distribution, patients will continue to present to rural services with serious medical issues. In such situations and in resource-poor settings, creative solutions are required to temporize ill patients, as we have reported, and represent an important facet of care in a rural setting.